System of collecting, storing, processing and vizualizating the scientific data of the National Antarctic Scientific Center - V. Litvinov; M. Sidorov; O. Skuybida (Ukrainian Antarctic Journal, 2008)
The research directions of National antarctic scientic centre are looked. The software of systems for collecting, storing, processing and vizualizating the scientic data of centre is presented.